MENANAMKAN PERAN KUNCI ORANG TUA DALAM BUDAYA LITERASI SEJAK USIA DINI DI DESA AIKMUAL, KECAMATAN PRAYA, KABUPATEN LOMBOK TENGAH - Anjani, Muhammad Rafi Zaidan; Jurnal Wicara; Marshendalia, Chika; Nafiah, Faziatun; Wijaya, I Nyoman Agus Ari; Aziz, Abdul; Sukmawati, Triani; Atthoriqsyah, Bimo; Suprihatin, Aftina; Fatihah, Nawal; Titin, Ni Nengah; Kinanti, Wulan (Universitas Mataram, 2025)
This study examines the key role of parents in instilling a literacy culture from early childhood in Aikmual Village, Praya District, Central Lombok Regency. Through the Community Service Program (KKN) of PMD UNRAM, socialization and training were conducted to educate parents on the importance of literacy for preschool-aged children. A qualitative descriptive approach using In Service Training (IST) methods was employed to enhance parents' understanding and skills in stimulating literacy at home. Results showed that the family, as the first educator, plays a crucial role in fostering reading habits, developing children’s thinking ability, imagination, and language skills. The interactive and participative socialization activities successfully raised community awareness about the importance of parental involvement in children’s literacy. Limiting gadget use and implementing read-aloud practices emerged as key strategies to address literacy challenges in the digital era. Thus, strengthening the role of parents is expected to create a sustainable literacy culture that supports children’s cognitive and social development in the future.